Pristup gramatičkim temama u hrvatskom kao inom jeziku - Banković-Mandić, Ivančica; Peruško, Katja (SlavVaria, 2023)
An Approach to Grammar Topics in Croatian as a Foreign and Second Language. Second and foreign language teaching methodology includes several approaches to teaching grammar. There are two opposed approaches - one advocates explicit teaching (ANČIĆ 2004), and according to the other, students should not necessarily be explicitly taught grammar but can be exposed to an acceptable amount and type of texts, which is in line with certain theories of language acquisition (GITSAKI 1998). There is also the third approach which combines the previous two. It refers to an individual approach of (not) teaching and raising awareness of language knowledge depending on various factors and whether foreign or heritage speakers are being taught (HRŽICA 2006). In this paper, we will present some approaches to teaching grammar that achieve progress in all language skills despite avoiding explicit grammar teaching.